Bolt Pull-Out Tests of Anchorage Body under Different Loading Rates - Tong-bin Zhao; Wei-yao Guo; Yan-chun Yin; Yun-liang Tan (Shock and Vibration)
Based on the force analysis and mechanical transmission mechanism of grouting bolts, the self-developed test apparatus for interfacial mechanics is used to study the distribution rule of axial force and interfacial stress of bolts in anchorage body. At the same time, pull-out tests of anchorage body are simulated with the particle flow code software PFC2D, and stress distribution and failure patters are researched under different loading rates. The results show that the distribution of axial force and interfacial shear stress is nonuniform along the anchorage section: axial force decreases, shear force increases first and then decreases, and the maximum value of both of them is closed to the pull-out side; with the increase of loading rates, both of axial force and interfacial shear stress show a trend of increase in the upper anchorage section but changes are not obvious in the lower anchorage section, which causes serious stress concentration; failure strength of pull-out and loading rates show a linear correlation; according to loading rates’ impact on the anchoring effect, the loading rates’ scope can be divided into soft scope (v<10 mm/s), moderate scope (10 mm/s < v < 100 mm/s), and strong scope (v>100 mm/s).